Psychology Dynamics of Male Victims of Emotional Dating Violence - Rizkya Ratih Andiani; Damajanti Kusuma Dewi (Character Jurnal Penelitian Psikologi, 2023)
Emotional dating violence is a form of violence that tends to be invisible because this emotional violence can take the form of verbal and psychological attack on the victim. The phenomenon that the researcher found was a male victim, this prompted the researcher to conduct research to obtain another point of view that victims of violence do not only occur in women. emotional violence. This study aims to explore the psychological dynamics of victims of emotional violence in men. This study uses a qualitative method with a case study approach. Researchers used semi-structured interviews, with data sources of 3 early adult males. The research results can be categorized into three main themes. The results of the study show that the psychological dynamics experienced by each participant are different in terms of the emotional violence experienced and the attitudes and actions taken to leave the relationship.